2020
DOI: 10.3389/fendo.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Role of the NLRP3 Inflammasome in Preeclampsia

Abstract: Reproduction involves tightly regulated series of events and the immune system is involved in an array of reproductive processes. Disruption of well-controlled immune functions leads to infertility, placental inflammation, and numerous pregnancy complications, including preeclampsia (PE). Inflammasomes are involved in the process of pathogen clearance and sterile inflammation. They are large multi-protein complexes that are located in the cytosol and play key roles in the production of the pivotal inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 172 publications
(209 reference statements)
5
55
0
Order By: Relevance
“…Preeclampsia without FGR was associated with increased decidual expression of NLRP3 and IL-1β, suggesting that the NLRP3 inflammasome aggravates the inflammatory response and substantiates the reported shift to a pro-inflammatory profile and cell type distribution at the maternal-fetal interface in preeclampsia ( 9 , 14 , 29 ). The increased decidual inflammasome expression was trophoblast dependent and strongest in areas where trophoblast and leukocytes are in proximity, suggesting that NLRP3 mediated inflammation may disturb maternal-fetal communication.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Preeclampsia without FGR was associated with increased decidual expression of NLRP3 and IL-1β, suggesting that the NLRP3 inflammasome aggravates the inflammatory response and substantiates the reported shift to a pro-inflammatory profile and cell type distribution at the maternal-fetal interface in preeclampsia ( 9 , 14 , 29 ). The increased decidual inflammasome expression was trophoblast dependent and strongest in areas where trophoblast and leukocytes are in proximity, suggesting that NLRP3 mediated inflammation may disturb maternal-fetal communication.…”
Section: Discussionsupporting
confidence: 76%
“…Preeclampsia is associated with increased maternal systemic inflammatory markers including total cholesterol, oxLDL, IL-1β and soluble fms-like tyrosine kinase-1 (sFlt-1) (26)(27)(28). The NLRP3 inflammasome pathway in preeclampsia has been recently reviewed and mechanistically illustrated (29). We have previously shown that the NLRP3 inflammasome is active in the placenta and associated with preeclampsia, with a central involvement of trophoblasts (28).…”
Section: Introductionmentioning
confidence: 99%
“…This activation process spreads rapidly via paracrine and endocrine pathways to other nearby or distant endothelial cells [ 78 ]. As discussed above, these particles may act via intravesicular microRNAs and/or circular RNAs that, after phagocytosis by endothelial and immune cells, induce sterile inflammation and alter the production of mediators of angiogenesis and vasoactivity, such as sFLT1, VEGF, and pregnancy-associated placental protein A (PAPP-A) [ 61 , 62 , 80 ]. Many other vasoactive and immunological mediators have been studied in the maternal serum for the diagnosis or prediction of PE, and are summarized in Table 3 .…”
Section: Pathophysiologymentioning
confidence: 99%
“…Importantly, Uri‐Belapolsky et al 16 reported that the deletion of the Il1a gene resulted in a higher pregnancy rate in aged mice compared to wild‐type aged mice. Conversely, excessive IL1B causes pregnancy complications, including an increased susceptibility to infectious diseases and inflammation 17–19 . These findings suggest that IL1A and IL1B play crucial roles in the induction of cellular senescence, SASP production, inflammation, aging, and infertility.…”
Section: Introductionmentioning
confidence: 99%